Rethinking modernity and national identity in Turkey - Bozdoğan, Sibel; Kasaba, Reşat, 1954- (Publications on the Near East, University of Washington., 1997)
The essays in this book are the first attempt to examine the Turkish experiment with modernity from a broad, interdisciplinary perspective, encompassing the fields of history, the social sciences, the humanities, architecture, and urban planning. The contributors offer a fresh, balanced understanding of dilemmas now facing not only Turkey but also many other parts of the Middle East and the world at large.